Gift of life: how nurses champion organ donation through Max and Keira's legacy. - Simpson, Dominic; Miller, Cathy; Plant, Sarah (British Journal of Nursing, 2025)
The article focuses on the critical role of specialist nurses in organ donation, highlighting their impact on successful donations and family support during challenging times. It illustrates this through the story of Keira Ball, whose organ donation saved four lives, including that of nine-year-old Max Johnson. Specialist nurses-organ donation (SNODs) serve as vital links between bereaved families and medical teams, enhancing consent rates and donor numbers through structured support and compassionate communication. The article emphasizes that the expertise and training of nurses are essential for improving organ donation outcomes and fostering a legacy of hope and healing for families.